2020
DOI: 10.3892/etm.2020.9382
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of MED and iLESSYS<sup>&reg;</sup> Delta for the treatment of lumbar central spinal stenosis and lateral recess stenosis: A comparison study

Abstract: Microendoscopic discectomy (MED) is an established procedure used to treat lumbar central spinal stenosis (LCSS) and lateral recess stenosis (LRS). The Interlaminar Endoscopic Surgical System iLESSYS ® Delta approach has been developed from the traditional interlaminar endoscopic technique for the treatment of LCSS and LRS. In the present study, MED was used as a reference to evaluate this newly developed approach. A total of 82 and 52 patients with radicular leg pain and/or neurogenic claudication symptoms we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
7
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
5
7
1
1
Order By: Relevance
“…At the same time, we noticed that the big working channel endoscopes techniques such as iLESSYS® Delta system [ 45 ] are also appropriate surgical methods for the treatment of central lumbar spinal stenosis, which are equipped with a larger size working cannula and endoscopic instruments, and permits big osteophytes or soft tissues to be removed without extra maneuvers under good endoscopic visualization [ 46 , 47 ], and the operation time is also shorter than our technology, but in order to broader endoscopic field of view, it also caused more damage to the tissue. However, The decompression of our spinal endoscopy is more accurate, and less damage to tissue, but the operation is difficult and the learning curve is steep, Comparing the two surgical techniques, we think that each operation has its own advantages, we can be more rational in the choice of surgical indications.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, we noticed that the big working channel endoscopes techniques such as iLESSYS® Delta system [ 45 ] are also appropriate surgical methods for the treatment of central lumbar spinal stenosis, which are equipped with a larger size working cannula and endoscopic instruments, and permits big osteophytes or soft tissues to be removed without extra maneuvers under good endoscopic visualization [ 46 , 47 ], and the operation time is also shorter than our technology, but in order to broader endoscopic field of view, it also caused more damage to the tissue. However, The decompression of our spinal endoscopy is more accurate, and less damage to tissue, but the operation is difficult and the learning curve is steep, Comparing the two surgical techniques, we think that each operation has its own advantages, we can be more rational in the choice of surgical indications.…”
Section: Discussionmentioning
confidence: 99%
“…Observation group [ 10 ]: After successful general anesthesia, the patient was fixed on the operating table in a prone position with the chest and iliac bone partially elevated and the target vertebral space positioned on the body surface. The skin was routinely disinfected and covered with sterile cavity wipes.…”
Section: Methodsmentioning
confidence: 99%
“…There are two types of surgery in this category: uniportal full-endoscopic surgery using the endoscope, which includes a working channel in the scope system, and biportal endoscopic surgery with two different skin incisions for the endoscope and for inserting instruments as in arthroscopic knee surgery. Wu et al [ 52 ] compared the clinical outcomes of microendoscopic decompression and uniportal full-endoscopic decompression and reported that the operating time was shorter, but skin incision was longer, for microendoscopic decompression. Improvements in VAS scores for leg pain were similar in the two groups.…”
Section: Clinical Outcomes Of Microendoscopic Lumbar Decompressionmentioning
confidence: 99%